PELATIHAN TIPS DAN TRIK MICROSOFT POWER POINT DI SALAM PATUK GUNUNGKIDUL - Jamroni, Jamroni; Sutono, Sutono; Saputra, Yogatama Sidiq (LPPM Akademi Manajemen Administrasi Yogyakarta, 2023)
ABSTRACT The residents of the Salam RT 15 hamlet community in particular include residents of rural communities who are far from the district and provincial cities. Varied levels of education make people really need additional knowledge for insight in following current developments that are increasingly advanced with information technology. Microsoft Powerpoint is an application for presentations that is really needed by the residents of the Salam Rt 15 hamlet community in particular. The purpose of this activity is to increase people's knowledge and skills in using the Microsoft Powerpoint application The target of this activity is the management and residents of RT 15 in Padukuhan Salam, Gunungkidul. The method used is by conducting training and mentoring on the use of the Microsoft Powerpoint application. The result of this dedication is that there is an increase in knowledge and skills in using the Microsoft Powerpoint application, namely from the results of the pretest compared to the results of the posttest that were carried out showing that 7 people were declared good during the pretest, then after the posttest there were 15 people, 16 people were declared lacking during the pretest, so after the posttest they stayed to 11 people.